Investigating bacteria-induced inflammatory responses using novel endometrial epithelial gland organoid models - Zhang, Xin; Zhang, Li; Li, Ting; Zhang, Zhan; Shang, Xiang; Bai, Huihui; Liu, Yong; Zong, Xiaonan; Shang, Chenguang; Song, Dan; Zhang, Xu; Fan, Linyuan; et al. (Frontiers in Reproductive Health, 2024)
IntroductionThe endometrium plays a crucial role in early human pregnancy, particularly in embryo implantation, survival, and growth. However, invasion and infection by pathogens can lead to endometritis, infertility, and poor reproductive outcomes. Understanding the mechanisms of endometritis and its impact on fertility remains limited. An infection model using patient-derived endometrial epithelial gland organoids (EEGOs) was established to advance in vitro studies on endometritis and related infertility.MethodsAn EEGOs infection model was constructed and characterized from human endometrium, treating the organoids with estrogen and progesterone to observe changes in the proliferative and secretory phases. The organoids were infected with E. coli, and the release of inflammatory cytokines in the supernatant was detected using ELISA. RNA-seq was employed to analyze the differences before and after E. coli treatment, and differential gene mRNA expression was validated using real-time quantitative PCR. Additionally, the effect of E2 in alleviating inflammation was assessed through markers of receptivity (PAEP, LIF, ITGβ), proliferation (Ki67), and barrier repair (ZO-1).ResultsThe constructed human EEGOs exhibited long-term expansion capability, genetic stability, and characteristic hormonal responses, strongly expressing epithelial markers (MUC1, E-Cadherin). After E. coli infection, the expression levels of inflammatory cytokines TNF-α, IL-8, and IFN-γ increased significantly (P < 0.05). RNA-seq indicated that the MAPK signaling pathway was activated post-infection, with increased expression levels of heat shock proteins and transcription factor mRNA. E2 treatment post-infection significantly decreased the mRNA expression of inflammatory genes IL-1β, IL8, IL6 and TNF-α compared to the E. coli infected group (P < 0.05). Additionally, the expression of genes related to receptivity, proliferation, and barrier repair was enhanced in the E2-treated organoids.ConclusionsOur findings demonstrate that patient-derived EEGOs are responsive to bacterial infection and are effective models for studying host-pathogen interactions in bacterial infections. These organoids revealed the anti-inflammatory potential of E2 in alleviating E. coli-induced inflammation, providing insights into the mechanisms of endometritis and its impact on infertility. The study supports the use of EEGOs as valuable tools for understanding endometrial health and developing targeted treatments.